Credit spreads and monetary policy - Vasco Cúrdia; Michael Woodford (Federal Reserve Bank of New York, 2009)
We consider the desirability of modifying a standard Taylor rule for a central bank's interest rate policy to incorporate either an adjustment for changes in interest rate spreads (as proposed by Taylor [2008] and McCulley and Toloui [2008]) or a response to variations in the aggregate volume of credit (as proposed by Christiano et al. [2007]). We then examine how, under those adjustments, policy would respond to various types of economic disturbances, including those originating in the financial sector that increase equilibrium spreads and contract the supply of credit. We conduct our analysis using a simple DSGE model with credit frictions (Cúrdia and Woodford 2009), comparing the equilibrium responses to various disturbances under the modified Taylor rules with those under a policy that would maximize average expected utility. According to our model, a spread adjustment can improve on the standard Taylor rule, but the optimal size of the adjustment is unlikely to be as large as the one proposed, and the same type of adjustment is not desirable regardless of the source of variation in credit spreads. A response to credit is less likely to be helpful, and its desirable size (and even sign) is less robust to alternative assumptions about the nature and persistence of economic disturbances.
Keywords: E50; E40; 330; Credit frictions; monetary policy; Geldpolitik; Zinspolitik; Zinsstruktur; Taylor-Regel; Neukeynesianische Makroökonomik; Dynamisches Modell; Stochastischer Prozess; Theorie